Bearberry in the treatment of acute uncomplicated cystitis (BRUMI): protocol of a multicentre, randomised double-blind clinical trial. Issue 6 (24th June 2022) - Tóth, Barbara; Jávorházy, András; Nyirády, Péter; Csupor-Löffler, Boglárka; Birinyi, Péter; Zhanel, George; Naber, Kurt; Länger, Reinhard; Vörhendi, Nóra; Gede, Noémi; Váncsa, Szilárd; Hegyi, Péter; et al.
Abstract : Background: Bearberry ( Arctostaphylos uva-ursi ) leaf is available as a treatment of uncomplicated cystitis in several European countries. The antimicrobial activity of its extracts and some of its individual constituents has been observed in vitro ; however, the efficacy of bearberry compared with standard antimicrobial therapy has not been assessed yet. Objective: The objective of the study is to assess the safety and non-inferiority of bearberry as an alternative therapy in the treatment of acute uncomplicated cystitis in comparison with standard antibiotic therapy (fosfomycin). Methods and analysis: This is a randomised controlled double-blinded multicentre trial. Eligible patients will be premenopausal women with a sum score of ≥6 for the typical acute uncomplicated cystitis symptoms (frequency, urgency, painful urination, incomplete emptying, suprapubic pain and visible haematuria) reported on the Acute Cystitis Symptom Score (ACSS) typical domain and pyuria. Patients will be randomly assigned to receive 3 g single dose of fosfomycin powder and two placebo tablets three times a day for 7 days or B a single dose of placebo powder and two tablets containing a dry extract of Uvae ursi folium. At least 504 patients (allocated as 1:1) will need to be enrolled to access non-inferiority with a non-inferiority limit of 14% for the primary endpoint. Improvement of symptoms of uncomplicated cystitis (based on the ACSS score) at day 7 is defined as the primary endpoint, whereas several secondary endpoints such as the number and ratio of patients with bacteriuria at day 7, frequency and severity of side effects; recurrence of urinary tract infection, concurrent use of other over the counter (OTC) medications and food supplements will be determined to elucidate more detailed differences between the groups. The number of recurrences and medications taken for treatment will be monitored for a follow-up period of 90 days (80–100 days). Ethics and dissemination: This study has been approved by the Scientific and Research Ethics Committee of the Hungarian Medical Research Council (IV/4225-1/2021/EKU). The results will be disseminated by publication of peer-reviewed manuscripts. Trial registration number: NCT05055544 .